Shear Strengthening of Reinforced Concrete Beams Using Externally Bonded Bi-Directional Carbon Fibre Reinforced Polymer - Jayaprakash, J. (2006)
Shear failure of Reinforced Concrete (RC) beams is catastrophic and could occur without any forewarning. Many existing reinforced concrete (RC) members are found to be deficient in shear strength and need to be repaired. Shear deficiencies in reinforced concrete beams may crop up due to many factors such as inadequate shear reinforcement, reduction in steel area due to corrosion, use of outdated design codes, increased service load, poor workmanship and design faults. The application of Carbon Fibre Reinforced Polymer Composite material, as an external reinforcement is a viabletechnology recently found to be worth for improving the structural performance of reinforced concrete structures. This study was conducted to investigate the shear strengthening capacity and modes of failure of reinforced concrete beams using externally bonded bi-directional Carbon Fibre Reinforced Polymer (CFRP) strip. To accomplish the objectives, an experimental program was conducted within laboratory environment where a specimen lot comprised of eighteen rectangular (18 Nos) beams and sixteen (16 Nos) T-beams were tested until failure. The specimens comprised of rectangular and T-beams of length 2980mm were fabricated and tested in the Structural Laboratory at Universiti Putra Malaysia. The rectangular beams were strengthened without any internal shear reinforcement but the T-beams were strengthened with internal shear reinforcement. The beams were classified into three categories: control, precracked/repaired and initially strengthened specimens. The variables investigated in this experimental program included (i) longitudinal reinforcement ratio, (ii) shear span to effective depth ratio, (iii) spacing of CFRP strip and (iv) orientation of CFRP strips. Test results showed that the externally bonded bi-directional Carbon Fibre Reinforced Polymer (CFRP) significantly enhances the shear enhancement of both the rectangular (without steel stirrups) and T-beam (with steel stirrups). The study also revealed that the contribution of externally bonded CFRP strips to the shear capacity was significantly influenced by the variables investigated. A design equation was developed to compute the shear contribution of CFRP to the shear capacity of RC beams. The experimental results were compared with the existing models of Triantafillou, 1998; Khalifa 2002; and ACI 440, 2003 to verify the proposed design equation. The theoretical values calculated by the proposed model for rectangular beams without internal shear reinforcement showed good agreement with those of the T-beams with internal shear reinforcement. The study observed that the predicted results of the existing models by Khalifa (2002) and ACI 440 were slightly higher than that of the proposed one. However it was also observed that the model by Triantafillou shows poor agreement in comparison to Khalifan (2002) and ACI 440 models. While the study contributed insights in terms of shear strength and modes of failure of reinforced concrete CFRP strengthened beams with respect to the variables such as shear span to effective depth ratio, longitudinal reinforcement ratio, spacing, and different orientations of CFRP strips, it developed a design equation and few recommendations.